2013
DOI: 10.1094/phyto-07-12-0158-r
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Genomic Variability of the Phytopathogenic Mollicute Spiroplasma kunkelii

Abstract: Corn stunt disease has become a factor limiting maize production in some areas of the Americas in recent years. Although resistant maize genotypes have been developed in the past, this resistance has been unstable over time or in some geographical locations. To better understand disease components that could affect the stability of host resistance, we assessed the genome variability of the etiologic agent, Spiroplasma kunkelii. Isolates were obtained from a number of areas, and characterized molecularly by amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…One of the most convenient alternatives to reduce yield loss resulting from diseases is the use of resistant crops [29]. The resistance of maize genotypes to S. kunkelii might remain stable over time and across regions due to the low genomic variation of this pathogen [30]. Fieldresistant genotypes have in fact been obtained in areas of high pressure [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most convenient alternatives to reduce yield loss resulting from diseases is the use of resistant crops [29]. The resistance of maize genotypes to S. kunkelii might remain stable over time and across regions due to the low genomic variation of this pathogen [30]. Fieldresistant genotypes have in fact been obtained in areas of high pressure [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…This might explain the relatively large size of Spiroplasmas, their spatial organization and complexity compared to the Mycoplasmas. Spiroplasmas are of particular interest because they include agricultural pathogens of major economic importance such as S. citri affecting citrus plants [49] and S. kunkelii affecting corn [50], [51] , as well as members that have been claimed to be involved in neurodegenerative diseases [52]–[54]. However, we have a different motivation for studying Spiroplasma , namely our interest in establishing Spiroplasma as a model for analytically studying spatio-temporal, biomechanical and motility aspects of a minimal cell system [55].…”
Section: Discussionmentioning
confidence: 99%
“…Maize varieties resistant to corn stunt have been bred, but this resistance is short lived. It is unclear why maize resistance is quickly overcome, as genomic analysis has shown that S. kunkelii isolates have low genetic diversity (Carpane et al, 2013). Corn stunt is linked to magnesium metabolism: the symptoms are similar to magnesium deficiency, magnesium is involved in S. kunkelii localization and infected plants seem to be unable to process high magnesium concentrations (Nome et al, 2009).…”
Section: Spiroplasma Kunkelii: a Mollicute With High Virulence And Lomentioning
confidence: 99%